The division and size of gains from liberalization in service networks - Bhattarai, Keshab; Whalley, John (Review of International Economics, 2006)
If two disjoint country service networks involving a small and large country are connected as part of international liberalization in the presence of network externalities, the per capita gain for the small country from access to a large network will be large, and the per capita gain for the large country will be small. In contrast to goods, the benefits of liberalization in network-related services are more likely to be approximately equally divided between large and small countries than is true of trade in goods, where benefits accrue disproportionately to the small country. We also argue that non-cooperation in network-related services trade may involve more extreme retaliation than suggested for trade in goods by the optimal tariff literature, so that relative to a non-cooperative outcome, gains from liberalization in network-related services become larger than from liberalization in goods. We develop simple models which we use for numerical examples showing these points, along with an empirical implementation for global telecoms liberalization for the US, Europe, Canada, and the rest of the world using the framework developed in the paper. This shows similar proportional gains to regions, consistent with the theme of the paper that goods and services liberalization differ. © 2006 The Authors Journal compilation © 2006 Blackwell Publishing Ltd.